Management of gastro-bronchial fistula complicating a subtotal esophagectomy: a case report - REYNOLDS, JOHN; RAVI, NARAYANASAMY (BioMed Central, 2009)
Background The development of a fistula between the tracheobronchial tree and the gastric conduit post esophagectomy is a rare and often fatal complication. Case presentation A 68 year old man underwent radical esophagectomy for esophageal adenocarcinoma. On postoperative day 14 the nasogastric drainage bag dramatically filled with air, without deterioration in respiratory function or progressive sepsis. A fiberoptic bronchoscopy was performed which demonstrated a gastro-bronchial fistula in the posterior aspect of the left main bronchus. He was managed conservatively with antibiotics, enteral nutrition via jejunostomy, and non-invasive respiratory support. A follow- up bronchoscopy 60 days after the diagnostic bronchoscopy, confirmed spontaneous closure of the fistula Conclusions This is the first such case where a conservative approach with no surgery or endoprosthesis resulted in a successful outcome, with fistula closure confirmed at subsequent bronchoscopy. Our experience would suggest that in very carefully selected cases where bronchopulmonary contamination from the fistula is minimal or absent, there is no associated inflammation of the tracheobronchial tree and the patient is stable from a respiratory point of view without evidence of sepsis, there may be a role for a trial of conservative management.
PUBLISHED
Keywords: Surgery